Vertical Force-velocity Profiling and Relationship to Sprinting in Elite Female Soccer Players - Manson, Sarah A.; Low, Cody; Legg, Hayley; Patterson, Stephen D.; Meylan, César (International Journal of Sports Medicine, 2021)
Explosive actions are integral to soccer performance and highly influenced by the ability to generate maximal power. The purpose of this study was to investigate the relationship between force-velocity profile, jump performance, acceleration and maximal sprint speed in elite female soccer players. Thirty-nine international female soccer players (24.3±4.7 years) performed 40-m sprints, maximal countermovement jumps and five loaded squat jumps at increasing loads to determine individual force-velocity profiles. Theoretical maximal velocity, theoretical maximal force, maximal power output, one repetition maximal back squat and one repetition maximal back squat relative to body mass were determined using the force-velocity profile. Counter movement jump, squat jump and maximal power output demonstrated moderate to large correlation with acceleration and maximal sprint speed (r=− 0.32 to −0.44 and −0.32 to −0.67 respectively, p<0.05). Theoretical maximal velocity and force, one repetition maximal and relative back squat demonstrated a trivial to small relationship to acceleration and maximal sprint speed (p>0.05). Vertical force-velocity profiling and maximal strength can provide valuable insight into the neuromuscular qualities of an athlete to individualize training, but the ability to produce force, maximal power, and further transference into sprint performance, must be central to program design.
Keywords: jumping; acceleration; speed; strength; testing